Effect of tidal volume and positive end‐expiratory pressure on expiratory time constants in experimental lung injury. Issue 5 (20th March 2016) - Henderson, William R.; Dominelli, Paolo B.; Molgat‐Seon, Yannick; Lipson, Rachel; Griesdale, Donald E. G.; Sekhon, Mypinder; Ayas, Najib; Sheel, A. William
Abstract: We utilized a multicompartment model to describe the effects of changes in tidal volume ( V T ) and positive end‐expiratory pressure (PEEP) on lung emptying during passive deflation before and after experimental lung injury. Expiratory time constants ( τ E ) were determined by partitioning the expiratory flow–volume ( V ˙ E V) curve into multiple discrete segments and individually calculating τ E for each segment. Under all conditions of PEEP and V T, τ E increased throughout expiration both before and after injury. Segmented τ E values increased throughout expiration with a slope that was different than zero ( P < 0. 01). On average, τ E increased by 45.08 msec per segment. When an interaction between injury status and τ E segment was included in the model, it was significant ( P < 0.05), indicating that later segments had higher τ E values post injury than early τ E segments. Higher PEEP and V T values were associated with higher τ E values. No evidence was found for an interaction between injury status and V T, or PEEP. The current experiment confirms previous observations that τ E values are smaller in subjects with injured lungs when compared to controls. We are the first to demonstrate changes in the pattern of τ E before and after injury when examined with a multiple compartment model. Finally, increases in PEEP or V T increased τ E throughout expiration, but did not appear to have effects that differed between the uninjured and injured state. Abstract : Manipulation of tidal volume or PEEP changes the pattern of passive expiration during mechanical ventilation before and after experimental lung injury.